A Game Theoretic Approach to Nuclear Safeguards Selection and Optimization. Issue 1 (2nd January 2016) - Ward, Rebecca M.; Schneider, Erich A.
ABSTRACT: This article presents a novel application of an inspection game to find optimally efficient nuclear safeguard strategies. It describes a methodology that allocates resources at and across nuclear fuel cycle facilities for a cost-constrained inspectorate seeking to detect a state-facilitated diversion or misuse. The methodology couples a simultaneous-play game theoretic solver with a probabilistic model for simulating state violation scenarios at a gas centrifuge enrichment plant. The simulation model features a suite of defender options based on current International Atomic Energy Agency practices and an analogous menu of attacker proliferation pathway options. The simulation informs the game theoretic solver by calculating the detection probability for a given inspector-proliferator strategy pair. To generate a scenario payoff, it weights the detection probability by the quantity and quality of material obtained. Using a modified fictitious play algorithm, the game iteratively calls the simulation model until Nash equilibrium is reached and outputs the optimal inspection and proliferation strategies. The value the attacker places on material quantity and quality is varied to generate results representative of states with different capabilities and goals. Sample model results are shown to illustrate the sensitivity of defender and attacker strategy to attacker characteristics.